Exploring the influence of EFL teachers' informal digital learning on creative classroom instruction: a cross-sectional study - Herri Mulyono; Zain Adinul Falah; Gunawan Suryoputro; Florante Ibarra (Springer, 2024)
Abstract This study addresses the limited exploration in the literature regarding the influence of EFL teachers' informal digital learning of English (IDLE) on their creativity in Indonesian EFL classroom instructions. Using a cross-sectional survey design, data were collected from 244 Indonesian EFL teachers, encompassing both pre-service and in-service teachers. Through multiple regression analysis and Rasch modelling analysis, the study evaluated the association between teachers' IDLE participation, demographics, and their teaching creativity. Findings of the present study revealed that Indonesian EFL pre-service and in-service teachers actively participate in Informal Digital Learning of English (IDLE), which impacts their teaching creativity. Nearly half (49.18%) engage strongly in activities like listening to English songs and watching YouTube videos, while 36.88% moderately engage in online educational content and social media conversations. A smaller group (13.93%) shows lower engagement in IDLE. The regression analysis revealed that while IDLE significantly predicted teaching creativity (p < 0.001), demographic factors did not indicate a substantial influence on creativity in teaching practices. Additionally, a Rasch-Wright map analysis unveiled that over half of the participants displayed strong creativity in teaching, with a notable inclination among younger teachers towards innovative and student-centered pedagogical strategies. The findings of the current study highlight the need for further exploration into the dynamics between informal digital learning, demographics, and creative teaching approaches, emphasizing the potential for fostering innovative pedagogical practices in language education.